Development of palm oil Extraction Performance Index (EPI) based on Oil Extraction Rate (OER) and Oil Loss (OL) - Andrew, Julia; Sulaiman, Alawi; Mokhtar, Mohd Noriznan; Baharuddin, Azhari Samsu; Norzaidi, Mohd Daud (Universiti Putra Malaysia Press, 2017)
his study proposes a new method to evaluate the performance of palm oil extraction based on Predictive Scoring Index methodology. The variables, Oil Extraction Rate (OER) and Oil Loss (OL), were identified as important to develop a new extraction index based on three different steriliser systems. There were six performance categories: Excellent, Very Good, Good, Average, Poor and Very Poor. Based on 75 selected palm oil mills data from 2009-2013, Continuous Sterilizer (CS) system and Conventional Sterilizer (CV) system recorded 2.7% and 1.3% respectively under the Excellent category. The Compact Modular Concept (CMC) system only recorded 'Very Good' (20%) and 'Good' (13.3%). This study showed that EPI could be used to monitor palm oil extraction performance to ensure maximum oil extraction and minimum losses.